Fundamental insights into aminolysis postpolymerization modification reaction of polymers featuring α, α-Difluoroacetate Esters. (16th September 2021) - Kakuchi, Ryohei; Fukasawa, Kota; Chou, Li-Chieh; Kim, Hyung; Amii, Hideki
Abstract: Detailed experimental insight into aminolysis postpolymerization modification reactions of polymers featuring α, α-difluoroacetates is provided to elucidate the synthetic scope of postpolymerization modifications. By combining the Friedel-Crafts polycondensation and the aminolysis post-polymerization modification, polymers with a rigid triphenylmethane backbone were chemically modified with acid sensitive functional units with high ester conversions (up to > 95%). Primary amines were found to be significantly more efficient in aminolysis than secondary amines. Thermal properties of polymers featuring α, α-difluoroacetates and α, α-difluoroacetamides were analyzed experimentally and their model systems were studied computationally. It was found that the aminolysis postpolymerization modification reactions of polymers with the rigid triphenylmethane backbone has no negative influence on their thermal properties. This indicates that α, α-difluoroacetate aminolysis studied herein offers a feasible and useful synthetic tool in postpolymerization modifications. Graphical abstract: Image 1 Highlights: The scope of aminolysis reaction of ɑ, ɑ-difluoroacetate polymers was presented. Polymers with a rigid backbone featuring ɑ, ɑ-difluoroacetamides are characterized. Structural insight into ɑ, ɑ-difluoroacetates and ɑ, ɑ-difluoroacetamides was provided.